2020
DOI: 10.1177/2050640619888040
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of a change in bowel habit for colorectal cancer within different age groups

Abstract: Background Change in bowel habit as a sole alarm symptom for colorectal cancer is disputed. Objective We investigated the diagnostic value of change in bowel habit for colorectal cancer, particularly as a single symptom and within different age groups. Methods This retrospective cohort study examined colorectal cancer fast track referrals and outcomes across four Swedish hospitals (April 2016–May 2017). Entry criteria constituted one or more of three alarm features: anaemia, visible rectal bleeding, or change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Anemia was assessed by 18 studies [17,18,[31][32][33][34]36,38,[40][41][42]46,47,49,53,[56][57][58] including 31157 patients, with a pooled prevalence of CRC of 6.2% (95%CI 3.8-8.6%). Anemia had 24.6% (95%CI 17.4-33.6%) sensitivity and 90.4% (95%CI 86.6-93.2%) specificity for CRC (see Figure 1B and Figure 2B).…”
Section: Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Anemia was assessed by 18 studies [17,18,[31][32][33][34]36,38,[40][41][42]46,47,49,53,[56][57][58] including 31157 patients, with a pooled prevalence of CRC of 6.2% (95%CI 3.8-8.6%). Anemia had 24.6% (95%CI 17.4-33.6%) sensitivity and 90.4% (95%CI 86.6-93.2%) specificity for CRC (see Figure 1B and Figure 2B).…”
Section: Anemiamentioning
confidence: 99%
“…Change in bowel habit was assessed by 21 studies [17,[31][32][33]35,36,38,[40][41][42][43][44]46,48,49,51,[53][54][55][56][57] including 29829 patients, with a pooled prevalence of CRC of 8.3% (95%CI 4.6-11.9%). Change in bowel habit had 26.3% (95%CI 14.8-42.4%) sensitivity and 78.6% (95%CI 65.7-87.6%) specificity for CRC (see Figure 1C and Figure 2C).…”
Section: Change In Bowel Habitmentioning
confidence: 99%
“…We found that patients of Asian, Black, and Mixed ethnic groups were less likely than White patients to have a record of changes in bowel habits, although the Asian group were more likely to have iron-deficiency anaemia. Both features have low PPVs for cancer in the general population, except when accompanied by other features [ 40 ]. In this study, over half of Asian and Black patients with changes in bowel habits and two-thirds of Asians with iron-deficiency anaemia had these recorded as isolated features, which may explain the recent report of longer times to diagnosis in these groups compared with the White group [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impact caused by the disease, rectal cancer significantly affects both the well-being and chances of survival for individuals affected by it. Rectal bleeding, altered bladder habits, stomach discomfort, and unintentional weight loss are only a few symptoms that may seriously affect everyday life and general wellbeing [ 4 ]. This further intensifies the challenging experience for individuals undergoing cancer treatment.…”
Section: Introductionmentioning
confidence: 99%